A checklist of Indian ticks (Acari: Ixodoidea) - GEEVARGHESE, G; FERNANDES, STAN; KULKARNI, S M (The Indian Journal of Animal Sciences, 2013)
In India, the discovery of the tick-borne viral disease, i.e. Kyasanur Forest Disease (KFD) in 1957 marked a milestone in the history of tick studies. There were only 50 species recorded before the discovery of KFD. The present record is 106 species accommodated in 12 genera of two families, i.e. Ixodidae and Argasidae. This. number is more than one-eighth of a total of approximately 820 tick species known from all over the world, included in 19 genera and 3 families.